Analisis Karakteristik dan Efikasi Diri Lansia Hipertensi yang Tinggal Bersama Keluarga - Putri, Silvia Elki; Putri, Nurdila Dwi; Gasril, Pratiwi; Maswarni (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2024)
Self-efficacy is the belief that elderly people need to improve their ability to care for their health. The aim of this research is to analyze the characteristics and self-efficacy of hypertensive elderly who live with their families in the Puskesmas Payung Sekaki, Pekanbaru. The research design is quantitative descriptive. The sampling technique used was purposive sampling with a total of 60 respondents. The measuring tool for self-efficacy is the GSE Scale questionnaire. The data analysis used was univariate, namely data on the characteristics and description of self-efficacy of hypertensive elderly who live with their families. The results showed that the majority were aged 60-74 years (elderly) (95.5%), most were women (61.7%), almost half were Javanese (36.7%), almost half had completed junior high school (46, 7%), and 50% do not work. The description of the efficacy of hypertensive elderly who live with their families is mostly high (58.3%). It is hoped that the results of this research will be a focus for Community Health Center (Puskesmas) nurses to involve families in providing nursing care to increase the self-efficacy of the elderly.